Effect of Diesel Soot on the Heterogeneous Reaction of NO2 on the Surface of γ-Al2O3 - Chao Wang; Lingdong Kong; Shengyan Jin; Lianghai Xia; Jie Tan; Yuwen Wang (Atmosphere, 2022)
Soot and aged soot are often found to be mixed with atmospheric particles, which inevitably affect various atmospheric heterogeneous reactions and secondary aerosol formation. Previous studies have investigated the heterogeneous reaction of NO2 with different types of soot, but there are few studies on the heterogeneous reaction of NO2 with mixtures containing diesel soot (DS) or aged DS and mineral dust particles. In this study, the effects of DS and aged DS on the heterogeneous reaction of NO2 on the surface of γ-Al2O3 were investigated via in-situ diffuse reflectance infrared Fourier transform spectrometry (DRIFTS). The results showed that the DS or DS n-hexane extract significantly inhibited the formation of nitrate on γ-Al2O3 particles and promoted the formation of nitrite. At 58% RH, with the increase of DS or DS n-hexane extract loading amount, the effect of DS or DS n-hexane extract on the formation of nitrate changed from promotion to inhibition, but DS or DS n-hexane extract always promoted the formation of nitrite. The results also showed that light was conducive to the formation of nitrate on the DS-γ-Al2O3 or DS-n-hexane extract-γ-Al2O3 particles. Furthermore, the influence of soot aging on the heterogeneous reaction of NO2 was investigated under light and no light. In the dark, O3-aged DS-γ-Al2O3 or O3-aged DS-n-hexane extract-γ-Al2O3 firstly inhibited the formation of nitrate on the mixed particles and then promoted it, while the effect of aged DS on nitrite formation was complex. Under light, the O3-aged DS-γ-Al2O3 firstly promoted the formation of nitrate on the mixed particles and then inhibited it, while the O3-aged DS-n-hexane extract-γ-Al2O3 promoted the formation of nitrate on the mixed particles. Our results further showed that the production of nitrate on the O3-aged particles under light or no light was greater than that of the UV-nitrate-aged particles. This study is helpful to deeply understand the atmospheric chemical behavior of soot and the heterogeneous conversion of atmospheric NO2.